Determination of the Dielectrophoretic Force Induced by the Photovoltaic Effect on Lithium Niobate - Alessio Meggiolaro; Sebastian Cremaschini; Davide Ferraro; Annamaria Zaltron; Mattia Carneri; Matteo Pierno; Cinzia Sada; Giampaolo Mistura (Micromachines, 2022)
The actuation of droplets on a surface is extremely relevant for microfluidic applications. In recent years, various methodologies have been used. A promising solution relies on iron-doped lithium niobate crystals that, when illuminated, generate an evanescent electric field in the surrounding space due to the photovoltaic effect. This field can be successfully exploited to control the motion of water droplets. Here, we present an experimental method to determine the attractive force exerted by the evanescent field. It consists of the analysis of the elongation of a pendant droplet and its detachment from the suspending syringe needle, caused by the illumination of an iron-doped lithium niobate crystal. We show that this interaction resembles that obtained by applying a voltage between the needle and a metallic substrate, and a quantitative investigation of these two types of actuation yields similar results. Pendant droplet tensiometry is then demonstrated to offer a simple solution for quickly mapping out the force at different distances from the crystal, generated by the photovoltaic effect and its temporal evolution, providing important quantitative data for the design and characterization of optofluidic devices based on lithium niobate crystals.